Establishment of xMAP for the simultaneous detection of antibodies to Newcastle disease virus and avian influenza virus. (24th November 2018) - Wang, Huanan; Cong, Feng; Guan, Jianchi; Xiao, Li; Zhu, Yujun; Lian, Yuexiao; Huang, Ren; Chen, Meili; Guo, Pengju
ABSTRACT: Using Luminex xMAP (x = analyte, MAP = multi-analyte profiling) technology, a serological method for the simultaneous detection of antibodies to Newcastle disease virus (NDV) and avian influenza virus (AIV) was established. Nano-magnetic beads coated with purified NDV protein and AIV nucleoprotein were incubated with serum samples. Using biotinylated rabbit anti-chicken IgY and streptavidin-R-phycoerythrin, the optical signals measured by a Luminex 200 detection system indicated the quantification of NDV or AIV antibodies in the serum. Specific pathogen-free (SPF) chicken serum was used as a negative control. The Luminex xMAP assay developed in this study demonstrated high specificity as there was no cross-reaction with antibodies to infectious laryngotracheitis virus, infectious bronchitis virus, infectious bursal disease virus, avian leukosis virus, and Marek's disease virus. The results from reproducibility experiments showed that intra-coefficients of variation were 3.36 and 9.23% and inter-coefficients of variation were 6.50 and 7.66% for NDV and AIV, respectively. The results also indicated that the Luminex xMAP assay was 16 times more sensitive for NDV antibody detection and 1, 024 times more sensitive for AIV antibody detection compared to the enzyme-linked immunosorbent assay (ELISA). A total of 300 chicken serum samples were subjected to both Luminex xMAP assay and ELISA, showing the coincidence rates of 98.67 and 98% for NDV and AIV antibody detection, respectively. This study provides a new method for the simultaneous detection NDV and AIV antibodies in the serum with high specificity and sensitivity.